Functional analysis of the response regulator DegU in Bacillus megaterium DSM319 and comparative secretome analysis of degSU mutants - Borgmeier, Claudia; Voigt, Birgit; Hecker, Michael; Meinhardt, Friedhelm (Applied microbiology and biotechnology, 2011)
We functionally analysed the two-component regulatory system DegSU (historically SacU) in Bacillus megaterium DSM319 by generating a genetic knock out as well as a sacU32 mutation. The latter—known to cause a hypersecretion phenotype in Bacillus subtilis —had no influence on extracellular protease and amylase activity in B. megaterium . Since the B. megaterium DegU complemented a Bacillus licheniformis ∆ degSU mutant, functionality of the protein was proven. Expression of the sacB encoded levansucrase was found to be dependent on DegSU in B. megaterium . Consistently, the fusion of the sacB promoter to gfp revealed a strong increase in GFP-expression in the sacU32 strain. On 2 D-gels of the secretome, a large number of intracellular proteins was seen. The culture medium contained only 42 secreted proteins which can be assigned to polypeptides involved in the metabolism of the cell wall, polypeptides with proteolytic activities and those with unknown functions. Though overall protease activity matches with the wild type, two proteolytic enzymes (Vpr and YwaD) are missing in the secretome of the ∆ degSU strain, while other degradative enzymes are not affected. In line with such findings, no increase of proteolytic or other degradative enzymes was seen in the sacU32 mutant. Thus, compared to B. subtilis and B. licheniformis , the number of extracellular proteins influenced by DegSU is surprisingly low in B. megaterium , a feature, probably advantageous as to the use of the sacU32 mutant for production of secreted proteins.